A Comparative Study on The Therapeutic Effect of pH, Temperature Triggered, and Ion Activated In Situ Gelling System For Ocular Delivery - Kurniawansyah, Insan Sunan; Farisa Desy Arya, Insi; Budiman, Arif; Zubaidah, and (Universitas Padjadjaran (Unpad), 2024)
One of the most popular pharmaceutical preparations for the eyes today is in situ gel. The in situ gel system is a system that is liquid at room temperature but will form a gel when it comes into contact with the body or undergoes a change in pH. The form of the drug delivery system is in-situ is a type of mucoadhesive drug delivery system. Gel formation depends on several factors such as temperature modulation, pH changes, the presence of ions, ultra-violet irradiation, electrical sensitivity, and the enzyme by which the active substance is released. The purpose of this study is to compare the therapeutic efficacy of in situ gel medicines on pH, temperature triggered, and ion activated gelling systems. A drug in situ gel is a drug delivery device that transforms into a gel after being applied to the body. The findings revealed that the pH, temperature triggered, and ion activated gelling system factors had a substantial influence on the extended release medicines that affect the therapeutic effect of in situ gel medications. This comparative investigation demonstrates that the pH, temperature triggered, and ion activated gelling system factors have significant implications on the therapeutic benefits of in situ gelled medicines. A deeper knowledge of the relationships between these variables and in situ gel drug delivery methods can lead to the development of more effective and dependable medication compositions. These findings could aid in the development of improved gel in situ drug delivery systems to improve therapeutic benefits in the treatment of a variety of medical disorders. Keywords: in situ gel, pH triggered, temperature triggered, ion activated, therapeutic effect.